PELATIHAN FOOD PHOTOGRAPHY UNTUK PRODUK KULINER ANGGOTA UMKM MANDIRI PANCORAN MAS (MAPAN) DEPOK - Wulandari, Wulandari; Winarni, Rina Wahyu; Wardani, Winny Gunarti Widya (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Marketing competition via digital media is currently encouraging culinary product businesses to display creative content via social media, especially displaying photos of food and beverage products. Knowledge about Food Photography that can arouse consumer interest is something that is really needed. Therefore, this Community Service activity held Food Photography training for members of UMKM Mandiri Pancoran Mas (MAPAN) Depok. UMKM MAPAN is a forum for micro, small and medium food producers with more than 50 members. The discussion of this activity uses descriptive qualitative methods with a visual communication design approach, especially photography theory to explain the principles and application of Food Photography in producing informative and communicative photographic works of food and beverage products. It is hoped that this training can help culinary entrepreneurs to maximize their marketing content on social media, because photo visualization that attracts attention and is able to convey messages is an important visual strength.